PENGARUH CHALLENGE STRESSORS DAN HINDRANCE STRESSORS TERHADAP KINERJA DENGAN CONSCIENTIOUSNESS SEBAGAI VARIABEL MODERASI PADA KARYAWAN PT. PLN (PERSERO) AREA BANDA ACEH - Shabrina, Yurnalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2016)
This research aimed to measure the effect of challenge stressors and hindrance stressors to job performance with conscientiousness as a moderating variable. This study also address the interaction of conscientiousness on job performance. The sample used in this research are employess of PT. PLN (Persero) Area Banda Aceh. The instrument of collecting data in this research is questionnaire. The sampling technique used in this study is Stratified random sampling. With a total of 95 questionnaires were distributed and just only 90 can be collected. Method of data analysis are Moderate Regression Analysis (MRA) which used as methods of analysis to determine the effect of all the variable involved. The result of this study indicate that challenge stressors and hindrance stressors have significant effect on job performance. Conscientiousness has significant effect on job performance. In addition abtained results that conscientiousness has moderated on the effect of challenge stressors and hindrance stressors to job performance on employees PT. PLN (Persero) Area Banda Aceh. Keywords: Hindrace Stressors, Challenge Stressors, Conscientiousness, Job Performance